The Influence of Accounting Information Systems and Organizational Culture on the Quality of Financial Statements - Barjah Alamsyah; Achmad Fajar (Budapest International Research and Critics University, 2022)
This study examines the quality of financial reports at the Cimacan Regional General Hospital. This study aims to determine whether there is an effect of accounting information systems on the quality of financial reports and to determine whether there is an effect of cost compliance on the quality of financial reports. This study uses a quantitative approach by using a simple random sampling method of selecting samples at Cimacan Hospital employees. Statistical tests carried out are multiple regression testing the coefficient of determination and hypothesis testing partially or simultaneously. The results of the tests carried out prove that the accounting information system affects the quality of financial reports, organizational culture affects the quality of financial reports. Likewise, simultaneously accounting information systems and organizational culture affect the quality of financial reports.